The Effect of Viral Marketing “Oreo X Blackpink” On Oreo Customer Loyalty (Survey on Instagram Followers @oreo_indonesia) - Hartadi, Nabeel Putra; Ardia, Velda (Educationist: Journal of Educational and Cultural Studies, 2023)
Viral Marketing is the digital version of Word of Mouth marketing, involving the creation of videos, advertisements and other marketing content that is so infectious that customers will search for it or share it with friends. Oreo is a product that implements viral marketing activities by collaborating with Blackpink. The purpose of this study was to determine the influence of "Oreo x Blackpink" viral marketing on Oreo customer loyalty. This research is a quantitative research with a survey method and data collection techniques used are questionnaires. The sample data collection technique in this study used random sampling. The results of this study indicate that there is a positive influence between the viral marketing "Oreo x Blackpink" on Oreo customer loyalty on @oreo_indonesia followers.